EVALUATION OF THE INFLUENCE OF SLIVER STRUCTURAL COMPOSITION AND CLEANLINESS ON YARN QUALITY (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This article presents a scientific analysis of how the structural quality and cleanliness of the feeding sliver affect the physical and mechanical properties of yarn in the ring spinning process. Based on experimental data and scientific studies, the relationship between fiber parallelization, density uniformity, neps content, and external impurities in the sliver and the resulting yarn quality is examined. The findings indicate that a high degree of fiber parallelization and cleanliness significantly improves yarn strength, evenness (U%), and surface smoothness. It is also shown that a two-stage sliver preparation process and modern monitoring systems reduce yarn breakage rates. In conclusion, the use of structurally stable and clean slivers is identified as a key factor in producing high-quality yarn in ring spinning systems.